An environmental friendly process for Antarctic krill (Euphausia superba) utilization using fermentation technology. (20th July 2016) - Sun, Jianan; Mao, Xiangzhao
Abstract: Antarctic krill was efficiently fermented by Bacillus subtilis OKF04 after the optimization of fermentation conditions. Bio-active substances were detected in fermentation broth, including polypeptides (9.5 g/L), phenols (1.1 g/L), polysaccharides (200.8 mg/L), and free amino acids (3469.4 mg/L). The fermentation broth was found to be rich in essential amino acids and non-protein amino acids, particularly methionine, leucine, lysine, and taurine. The fermentation broth was separated into 4 fractions: AKF-I (<1 kDa), AKF-II (1–3 kDa), AKF-III (3–5 kDa), and AKF-IV (>5 kDa), using membrane ultrafiltration. Antioxidative properties of the fermentation broth fractions were investigated, using DPPH (2, 2-diphenyl-1-picryl-hydrazyl-hydrate) scavenging activity, metal chelating activity and reducing capacity. The results showed that AKF-I and AKF-II had higher antioxidant activities than other fractions and the entire fermentation broth. These results indicate that bio-active substrates could be effectively and cleanly produced using fermentation of Antarctic krill by B. subtilis, and the antioxidant activity (DPPH scavenging activity, metal chelating activity and reducing capacity) of the fermentation broth is enhanced by ultrafiltration. Highlights: Antarctic krill was fermented by Bacillus subtilis for the first time. Bio-active substances could be cleanly and efficiently produced in the fermentation broth. Antioxidant capacity of the fermentation broth could be enhanced by membrane ultrafiltration.